Single bone metastasis from adenocarcinoma of the lacrimal gland: a case report. (August 2014) - Ricci, Marianna; Amadori, Elena; Chiesa, Fausto; Bongiovanni, Alberto; Liverani, Chiara; Fabbri, Laura; Falasconi, Maria Cristina; Casadei, Roberto; Oboldi, Devil; Galassi, Riccardo; Micheletti, Simona; Severi, Stefano; et al.
ABSTRACT : Malignant tumors of the lacrimal gland are rare, and single bone metastases from lacrimal gland carcinoma are an exceptional event. We present the case of a 71-year-old man with a history of lumbar pain and left exophthalmos. Surgical resection of the lacrimal lesion and a bone biopsy gave a final histopathological diagnosis of primary ductal adenocarcinoma of the lacrimal gland with bone metastasis. The pathological tissue from both procedures was positive for androgen receptor expression. The patient underwent embolization and radiotherapy in association with total androgen blockade. After 20 months, the patient is still asymptomatic and has maintained the partial response at L1 with no progression to other sites. Our patient would appear to have a better prognosis and the disease a more indolent clinical course than the other cases of ductal adenocarcinoma of the lacrimal gland reported in the literature.